Peran Orang Tua Dalam Pembelajaran Bahasa Arab Secara Daring Masa Pandemi Covid-19 - Ria Ratna Ningtyas; Rifqi Aulia Rahman; Chairani Astina (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
The study aims to determine the implementation of online Arabic learning activities, to know the role of parents, and to find out the inhibiting-supporting factors in online Arabic learning activities during the COVID-19 pandemic for students of MTs Ma'arif Sapuran Wonosobo. The type of research used is descriptive qualitative, conducted by observation, in-depth interviews and documentation. Data analysis techniques through data reduction, data presentation, and conclusions. The results of the study show that, (1) Online Arabic learning activities at the school are still running despite many obstacles, but online Arabic learning is considered less than optimal and confusing. Many students are not active to the teacher when giving Arabic material or assignments via WhatsApp. Furthermore, the Arabic language teacher initiates to cooperate with parents so that students remain active in participating in learning even with a long duration of time, (2) The role of parents in online Arabic learning has been maximized, this is evidenced by their role being the first teacher for their children at home, encouraging, educating and assisting their children to study, providing adequate motivation and facilities, giving strong encouragement so that children continue to study diligently even though they are online, making the home environment comfortable so that children can focus on this situation, maintain good communication with children, (3) practically there is only one inhibiting factor, namely signal constraints, the supporting factors are being able to communicate remotely without being limited by distance, place, and time, learning can be accessed anytime and anywhere, and the existence of internet quota assistance, and LKS book assistance.